2016
DOI: 10.1002/cncr.30053
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of survivorship for older adults with cancer

Abstract: In May 2015, the Cancer and Aging Research Group (CARG), in collaboration with the National Cancer Institute and the National Institute on Aging through a U13 grant, convened a conference to identify research priorities to help design and implement intervention studies to improve the quality of life and survivorship of older, frailer adults with cancer. Conference attendees included researchers with multidisciplinary expertise and advocates. It was concluded that future intervention trials for older adults wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 49 publications
2
81
0
Order By: Relevance
“…Although the American Society of Clinical Oncology and other guidelines have recommended GA for older patients with cancer receiving chemotherapy, limited data are available on how GA can help guide interventions to improve QOL and emotional health in caregivers of older adults with cancer. Given the aging of both patients with cancers and their caregivers, a GA‐guided dyadic approach to interventions should be studied . Engaging both older patients and their caregivers in the research process from design to dissemination of interventions may improve the successful implementation and integration of interventions for vulnerable caregivers at high risk for poor emotional health and QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Although the American Society of Clinical Oncology and other guidelines have recommended GA for older patients with cancer receiving chemotherapy, limited data are available on how GA can help guide interventions to improve QOL and emotional health in caregivers of older adults with cancer. Given the aging of both patients with cancers and their caregivers, a GA‐guided dyadic approach to interventions should be studied . Engaging both older patients and their caregivers in the research process from design to dissemination of interventions may improve the successful implementation and integration of interventions for vulnerable caregivers at high risk for poor emotional health and QOL.…”
Section: Discussionmentioning
confidence: 99%
“…The results are intended to inform development of online or electronic medical record based systems to assist in frailty assessment, and facilitate treatment decision-making and care planning with older patients. 7,23 The ease of administration and predictive validity of deficits accumulation indices could provide a novel approach to expand the reach of frailty measurement in routine oncology practice settings.…”
Section: Introductionmentioning
confidence: 99%
“…We led a U13 grant (U13 AG038151), in close collaboration with the National Institute of Aging (NIA), the National Cancer Institute (NCI), and other major organizations (AGS, Gerontological Society of America, and the Alliance), which coordinated three research conferences composed of top leaders at the interface of aging and cancer research. The resulting series of 16 articles, including 4 major white papers, summarized the essential research priorities in geriatric oncology and identified that a coordinated research infrastructure and expertise to develop and prioritize these studies was desperately needed (Table ) . We also collaborated as principal investigators and coinvestigators on several other grants from the Patient‐Centered Outcomes Research Institute (PCORI), NCI, and NIA; hosted several conferences, bringing national leaders together; and coauthored dozens of other articles together.…”
Section: Carg: the Cancer And Aging Research Groupmentioning
confidence: 99%